The Density of MoSi2 Electron States for the Amorphous Film - Stetsun, A.I. (Physics and Chemistry of Solid State, 2016)
The density of MoSi2 electron states for the amorphous film has been calculated. An electron states at the top of valence band for this material are provided d electrons of molybdenum, p electrons of silicon and p electrons of molybdenum. d electrons of molybdenum are significant especially for physical properties of MoSi2.